Analisis Pengaruh Perekat Tepung Tapioka Pada Pengurangan Kadar Abu Briket Tempurung Kelapa - Pratama, Randa Julio; Napitupulu, Robert; Kurniawan, Zaldy; Darta, Yuli (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Binders play a vital role in briquette production by uniting charcoal particles into a solid form. This study aims to evaluate the effect of tapioca starch concentration as a binder on reducing the ash content of coconut shell briquettes. The binder concentrations used were 10%, 15%, and 20% of the total material mixture, with ash content testing conducted according to SNI 01-6235-2000 standards. The briquette production process involved raw material preparation, mixing, molding, and drying. The results indicated that binder concentration significantly influenced the ash content of the briquettes. Lower binder concentrations resulted in reduced ash content, with the lowest ash content of 1.52% achieved at a binder concentration of 10%. Conversely, higher binder concentrations tended to increase ash content due to residual binder that did not fully combust. This study emphasizes the importance of regulating binder concentration to enhance the quality of coconut shell briquettes as an alternative fuel source.